Screening of Common Eye Problems in Children by School Teachers and Community Health Workers - Ahla Fatima, Tahir Mehmood Sabir, Ghulam Hussain Asif (Pakistan Journal of Ophthalmology, 2018)
Purpose: To detect the refractive error, amblyopia, trachoma and squint in the School and non-School going Children between the age of 3 to 16 years. DESIGN: Cross sectional study PLACEAND DURATION OF STUDY: DHQ Hospital Vehari and duration of study was one year. MATERIAL AND METHOD 33 Villages of District Vehariwere selected for this study. In the pilot phase, three Villages were recruited. Two Primary Schools (one female and one male) from each village were included. One Teacher from each School, One Community Health Worker and one Community Based Organization Member were trained to detect visual deficit, squint, and red eye. Eye examination kit consisting of vision chart, three-meter rope, first aid material for eye, was provided. The screening carried out at the community and the affected children were referred for further examination to DHQ Hospital Vehari. RESULTS The affected children were referred and brought to department of Ophthalmology, DHQ Hospital Vehari for further ophthalmic examination and 90% of these screened children had positive findings like, refractive error, squint, amblyopia, trachoma and other ocular abnormalities. CONCLUSION: Primary School Teachers and the Community Based Organizations are very helpful in recognizing and solving the eye problems in younger age groups in remote areas. KEY WORDS:CCEHP(Community Children Eye Health Program), Refractive error, School Eye Health